UPAYA PENYIDIK MELAKUKAN REHABILITASI TERHADAP PENYALAHGUNA NARKOTIKA BAGI DIRI SENDIRI MENURUT UNDANG-UNDANG NARKOTIKA (Studi Pada Satres Narkoba Polres Kepulauan Mentawai ) - Defri, Defrizal (UNES Law Review, 2018)
Investigators have an important role to the settlement of cases of narcotics abuse for themselves. In dealing with narcotics abusers for themselves, investigators should be oriented to action sanctions in the form of rehabilitation. This is very necessary in order to operationalize Article 54 of Law Number 35 Year 2009 on Narcotics, where the narcotics abusers for themselves are obliged to undergo medical rehabilitation and social rehabilitation. Based on the results of the study, as well as the discussion and analysis, obtained the conclusion as an answer to the formulation of the problem, as follows: first, the investigator's efforts to the rehabilitation of narcotics narcotics for themselves according to the Narcotics law on Satres Drugs Mentawai Islands Police done by sending a request for an assessment to BNN West Sumatra Province. The request to conduct an assessment to West Sumatra Provincial BNN for suspected Narcotics abusers for themselves is conducted against the suspect with evidence and limit of usage of at most 5 grams. If the evidence brought by the suspect is more than 1 grams, the Satres Drug Investigator of Mentawai Islands Resort does not send a request for an assessment to BNN West Sumatera Province. Second, obstacles encountered by the investigator against the efforts of the rehabilitation of narcotics narcotics for themselves according to the Narcotics law in the Drug Satres Mentawai Islands Police, in the first instance, has not been formed Integrated Assesmen Tim in Mentawai Islands District. Secondly, the lack of community response in the rehabilitation of narcotics narcotics for themselves, where narcotics abusers for themselves and families of narcotics abusers for themselves, no one reports to Satres Drug investigators Mentawai Islands police.